Occurrence of sarcoidosis subsequent to chemotherapy for non-Hodgkin's lymphoma: report of two cases - Kornacker, Martin; Krämer, Alwin; Leo, Eugen; Ho, Anthony Dick (Annals of hematology, 2002)
Sarcoidosis-lymphoma syndrome is a well-established syndrome where sarcoidosis is followed by the development of a lymphoproliferative disease such as non-Hodgkin's lymphoma (NHL). Here we report two patients with NHL who developed sarcoidosis subsequent to the diagnosis of lymphoproliferative disease. In both cases, chemotherapeutic treatment had already been initiated or was completed when sarcoidosis occurred. In these patients, sarcoidosis may have been triggered by immunologic aberrations induced by antineoplastic therapy or as a consequence of an underlying immunologic disturbance associated with the lymphoma. When a suspected relapse of lymphoma presents with signs and symptoms compatible with sarcoidosis, this rare immunologic disorder has to be ruled out by careful clinical and histopathologic analysis to prevent mistreatment.
Gesehen am 14.12.2021